Senderización y Señalética de una Cicloruta Turística en la Parroquia Pindal del Cantón Pindal de la Provincia de Loja - Silva Esparza, Arianna Nicole (2017)
Tourism worldwide is one of the industries with the greatest growth and importance in the economic, environmental and socio-cultural fields. This is evidenced by the increase in the generation of significant income for the majority of the countries that have intervened in a responsible and sustainable way on their products and tourist attractions. From the beginning, the tourism industry began to develop in the rural sector, achieving a constant dynamism in the economy of rural villages, that is why it is required that these areas must be signposted, since tourist signaling is paramount, Providing the tourist with adequate information and guidance. The Pindal parish of Canton Pindal has a great variety of natural and cultural tourist attractions as well as a rich gastronomy that attracts the attention of tourists, but there are no formal spaces for the practice and development of physical, recreational, cultural and tourist activities. The lack of a connection between the tourist attractions extends to the implementation of "SENDERIZATION AND SIGNALING OF A TOURIST CYCLONE IN THE PINDAL PARK OF THE CANTÓN PINDAL DE LA PROVINCIA DE LOJA", in order to spread the attractions, improving the offer and the Tourist demand of the parish and turn of the canton. For the development of the research, it was proposed as general objective to elaborate a proposal of senderización and signage of a tourist cycloruta in the Pindal parish of the Pindal canton of the province of Loja, and as specific objectives the following: to elaborate a situational diagnostic of the parish Pindal in order to know the current situation of the area, to propose the design of senderización and signage for the tourist cycle of the parish Pindal and to identify the environmental impacts caused by the senderización and signage of the tourist cycle in the Pindal parish. For the development of the first specific objective: to develop a situational diagnostic diagnosis of the Pindal parish; The analytical method was used, in order to know the current situation of the Pindal parish, and the Carla Ricaurte Matrix was used to carry out the tourist diagnosis in order to gather information necessary for the development of the project. Also used the technique of direct observation for the development of MINTUR tourist attraction inventory cards, which enabled us to authenticate the hierarchy in which the different tourist attractions are currently found, interviews were conducted with people involved with tourism with The purpose of collecting information that served to carry out the analysis of the Matrix Foda. For the fulfillment of the second specific objective: To propose the design of senderización and signage of the tourist cycle in the parish of Pindal, the analytical method was applied, synthetic and inductive, they allowed to obtain the pertinent information and analysis to establish the attractions of greater interest and The obligatory crossing points for the senderization of the tourist cycle will determine the technical specifications of the trail taking as reference the standards of MINTUR that fit the project. Also the GPS system was used to determine the geo reference of each point, using the methodology of CIFUENTES was determined the load capacity with which the maximum number of visits that can receive the path leading to the attractiveness was established. For the signage of the tourist cycle was taken into account the Manual of Tourist Signage of MINTUR, for the elaboration and location of the corresponding signage, in addition was used a card for the explanation of the corresponding signage in which the information data. For the fulfillment of the third specific objective: To identify the environmental impacts caused by the senderization and signage of the cyclone of the Pindal canton, the Leopold matrix was used, thus identifying the impacts that this project can cause in the natural environment. Regarding the results of the investigation, the diagnosis of the Pindal Parish of the Pindal canton was made, in which the location, limits, flora, fauna, tourist attractions, infrastructure and social aspects could be known. Likewise, information was collected based on the methodology of the diagnosis of the Matrix of Carla Ricaurte. In addition, it was necessary to carry out the pertinent interview with the mayor of the canton Pindal, Eng. Libar Bustamante, the Director of Social and Cultural Development of Pindal Ower Mora and Mr. Luis Castillo tourist guide, this helped to reinforce the information of the current situation to investigate. The location of the signage was determined, in order to inform about the activities that can be performed during the cycle, attaching to them the investment budget in case of implementing the proposal. It is concluded that the Canton Pindal has relevant tourist attractions for the development of a tourist cycle, the same will serve to make known to its own and strangers their different tourist attractions. The recommendations of the thesis work are to carry out campaigns of diffusion of the tourist attractions that it possesses, in the different points of information so that the tourist has knowledge of them, also to give opening and support for the realization of new tourist projects oriented to the improvement and Diffusion of tourist attractions.